2018
DOI: 10.1096/fj.201701250r
|View full text |Cite
|
Sign up to set email alerts
|

New GABA modulators protect photoreceptor cells from light‐induced degeneration in mouse models

Abstract: No clinically approved therapies are currently available that prevent the onset of photoreceptor death in retinal degeneration. Signaling between retinal neurons is regulated by the release and uptake of neurotransmitters, wherein GABA is the main inhibitory neurotransmitter. In this work, novel 3-chloropropiophenone derivatives and the clinical anticonvulsants tiagabine and vigabatrin were tested to modulate GABA signaling and protect against light-induced retinal degeneration. Abca4Rdh8 mice, an accelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that acute exposure to light can promote apoptosis of retinal pigmented epithelium cells and photoreceptors, intensifying the progression of neurodegenerative diseases of the eye [8], and several studies have demonstrated that blue, or blue-rich white LEDs, are more toxic because they can initiate damage and death of photoreceptors more easily [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that acute exposure to light can promote apoptosis of retinal pigmented epithelium cells and photoreceptors, intensifying the progression of neurodegenerative diseases of the eye [8], and several studies have demonstrated that blue, or blue-rich white LEDs, are more toxic because they can initiate damage and death of photoreceptors more easily [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several studies showed that the inhibitory signaling progresses laterally through the retina. It was mediated mainly by GABA via amacrine cells and horizontal cells (Schur et al, 2018;Moore-Dotson and Eggers, 2019). The mCherry signal in amacrine cells was weakened, implicating that the inhibition signal may be interrupted.…”
Section: Discussionmentioning
confidence: 98%
“…Then, glutamine was released in culture medium, and acted as the driving force for glutamate uptake and GS activity to avoid any glutamate toxicity [ 32 , 33 , 34 ]. Interestingly, in high glutamate concentration [ 19 ] as used in this study to mimic glutamate toxicity involved in retinal degeneration [ 20 , 21 ], the main striking effect of dietary supplementation on Müller cells is the modulation of the glutamate/glutamine cycle in favor of glutamine release. The increase in GS, responsible for conversion of glutamate into glutamine [ 35 ], leads to an increase in intracellular glutamine as well as in glutamine release from Müller cells.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate experimental conditions: High glutamate concentration (1 mM) in culture medium with nor glutamine, nor red phenol, or FBS was used for metabolic test. This concentration was chosen [ 18 , 19 ] in order to mimic glutamate toxicity involved in retinal degeneration conditions [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%